Spiritual intelligence: a qur’anic alternative approach - Bensaid, Benaouda; Machouche, Salah (London Academy of Iranian Studies, 2012)
Despite the efforts made to produce universal models of spiritual intelligence reflecting diverse beliefs, values and cultures, they fall short of appreciating the inner depth of many religious and cultural experiences. The Qur’anic insight into developing spiritual capability shaping human life makes this issue an extremely interesting and vitally critical topic in need of analysis. This paper sheds light on a number of issues on spiritual intelligence according to the Qur’an, and seeks to develop a competency-based criterion for it. What is meant by ‘spiritually intelligent’ and what does spiritual intelligence look like? What are the spiritual qualities and revealing indicators of spiritual intelligence? What are the fundamental goals, defining characteristics and structure of spiritual intelligence according to the Qur’an? This paper furthermore provides several illustrations that effectively highlight the Qur’anic perspective with regards to the understanding and consequent application of spiritual intelligence as found in the stories of Cain and Abel, Prophet Ibrahim and Prophet Joseph. The paper also discusses some core aspects such as structure, illustrations, dimensions, indicators, as well as sustaining and de-sustaining factors. The paper concludes that the Qur’anic alternative of spiritual intelligence is all-embracing, yet diverse, and integrates it in a system of belief, worship, morality and social responsibility.